Biological Agency: Its Subjective Foundations and a Large-Scale Taxonomy - Brizio, Adelina; Tirassa, Maurizio (Frontiers in Psychology, 2016)
We will outline a theory of agency cast in theoretical psychology, viewed as a branch of a non-eliminativist biology. Our proposal will be based on an evolutionary view of the nature and functioning of the mind(s), reconsidered in a radically subjectivist, radically constructivist framework. We will argue that the activities of control systems should be studied in terms of interaction. Specifically, what an agent does belongs to the coupling of its internal dynamics with the dynamics of the external world. The internal dynamics, rooted in the species' phylogenetic history as well as in the individual's ontogenetic path, (a) determine which external dynamics are relevant to the organism, that is, they create the subjective ontology that the organism senses in the external world, and (b) determine what types of activities and actions the agent is able to conceive of and to adopt in the current situation. The external dynamics that the organism senses thus constitute its subjective environment. This notion of coupling is basically suitable for whichever organism one may want to consider. However, remarkable differences exist between the ways in which coupling may be realized, that is, between different natures and ways of functioning of control systems. We will describe agency at different phylogenetic levels: at the very least, it is necessary to discriminate between non-Intentional species, Intentional species, and a subtype of the latter called meta-Intentional. We will claim that agency can only be understood in a radically subjectivist perspective, which in turn is best grounded in a view of the mind as consciousness and experience. We will thus advance a radically constructivist view of agency and of several correlate notions (like meaning and ontology).